ANALISIS LABORATORIUM TEKNOLOGI PEMBUATAN GERABAH SITUS GEDUNGKARYA, MUARA JAMBI, PROVINSI JAMBI - Ni Komang Ayu Astiti (WalennaE, 2001)
Pottery is one of human attempts to meet their basic needs and make used the lands surrounds them. Despite the clay as pottery compositions, a mixture material was added which strongly affected substance that it contained. Therefore, despite the physical analysis to understand the pottery nature, a substance analysis must take place in order to identify the clay composition or its contents used. These analyses were applied at Gedungkarya site showed that kaolinit clay used by the potters was using different chemical composition. It was also recognized that pottery materials came from the same area, even within different times.